Procedura oceny controllingu w przedsiębiorstwie - Nowosielski, Krzysztof (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper presents the essence of efficiency and effectiveness of controlling assessment in enterprises. The main objective was to discuss available methods of this measurement and to present own proposition of how to measure controlling functioning in the enterprises. The author points out both possible problems of this process and benefits for users. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 320-328